Modulation of adiponectin receptors AdipoR1 and AdipoR2 by phage display-derived peptides in in vitro and in vivo models. (13th September 2020) - Crombez, Deborah; Delcambre, Sébastien; Nonclercq, Denis; Vander Elst, Luce; Laurent, Sophie; Cnop, Miriam; Muller, Robert N.; Burtea, Carmen
Abstract: Type 2 diabetes (T2D) is often linked to metabolic syndrome, which assembles various risk factors related to obesity. Plasma levels of adiponectin are decreased in T2D and obese subjects. Aiming to develop a peptide able to bind adiponectin receptors and modulate their signalling pathways, a 12-amino acid sequence homologous in AdipoR1/R2 has been targeted by phage display with a linear 12-mer peptide library. The selected peptide P17 recognises AdipoR1/R2 expressed by skeletal muscle, liver and pancreatic islets. In HepaRG and C2C12 cells, P17 induced the activation of AMPK (AMPKα-pT172) and the expression of succinate dehydrogenase and glucokinase; no cytotoxic effects were observed on HepaRG cells. In db/db mice, P17 promoted body weight and glycaemia stabilisation, decreased plasma triglycerides to the range of healthy mice and increased adiponectin (in high fat-fed mice) and insulin (in chow-fed mice) levels. It restored to the range of healthy mice the tissue levels and subcellular distribution of AdipoR1/R2, AMPKα-pT172 and PPARα-pS12. In liver, P17 reduced steatosis and apoptosis. The docking of P17 to AdipoR is reminiscent of the binding mechanism of adiponectin. To conclude, we have developed an AdipoR1/AdipoR2-targeted peptide that modulates adiponectin signalling pathways and has therapeutic relevance for T2D and obesity associated pathologies.